Micronutrient supplementation in pregnancy: a KAP survey with healthcare consultants in India - Chandra, Sunita; Mane, Sheela V.; Biniwale, Parag; Sundari, M. Tripura; Mulye, Anuradha; Adhav, Charles (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Maternal nutrition during pregnancy is a serious public health issue as it negatively impacts women and their children. The most commonly used nutritional interventions during pregnancy are folic acid and omega-3 fatty acid (n-3 FA). This survey aimed to evaluate the knowledge, attitude and perception towards folic acid, n-3 FA and other supplementation amongst healthcare practitioners (HCPs). Methods: A close-ended questionnaire-based survey was distributed among obstetricians-gynaecologists and HCPs overlooking pregnant and lactating women between July and September 2022 in India. An excel based survey analysis was performed once the survey completed. Results: A total of 500 valid questionnaires were collected. Only 55% of them recommended n-3 FA, whereas 45% did not recommend as they believed that the typical Indian diet provides enough n-3 FA and supplements are not necessary. The majority (58.91%) of prescribers prescribed n-3 FA to all pregnant women, followed by older women with a history of abortion and high-risk pregnancy. Both eicosapentaenoic acid and docosahexaenoic acid were favoured in clinical practice. In addition, 56.8% of HCPs recommended folic acid at a dose of 5 mg/day for patients with a bad obstetric history, while 43.2% of HCPs recommended folic acid at a dose of 1 mg/day. Conclusions: Supplements and adequate nutrition can reduce the likelihood of poor maternal and foetal outcomes in high-risk pregnancies. Nutritional supplementation is a cost-effective and safe risk-reduction method, given the high prevalence of pregnancy complications. However, more knowledge dissemination on n-3 FA supplements, folic acid and micronutrients is essential.